Fundamentals of professional baking : bread and pastry production - Sandique, Jill F. (Mandaluyong City, Philippines : Anvil Publications, 2019)
The lessons were designed to help the student master the techniques in classical pastry and baking and be able to use them in any professional kitchen with skill and confidence.
Acknowledgement -- Introduction -- Unit. 1 Basics -- Unit 2. Recipes and techniques -- Pronunciation Guide -- Glossary -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: BAKING -- STUDY AND TEACHING